ANALISIS POTENSI PASAR KOMODITI RUMPUT LAUT DI DESA KAMPUNG BUNGA KECAMATAN LASOLO KABUPATEN KONAWE - Yunila Yunila (Yayasan Akrab Pekanbaru, 2018)
This research was conducted in Kampung Bunga Village, Lasolo District of Konawe Regency, with the aim to analyze the prospect of marketing development of seaweed commodity and to analyze the prospect of increasing farmer's income. The data analysis used is descriptive qualitative analysis. The results showed that: Seaweed commodity in Kampung Bunga Village, Lasolo District of Konawe Regency, has marketing potential, Development of marketing potential of seaweed commodity can increase the actual income of seaweed farmers. Keyword: Potency of Pamasaran and Revenue